Dreaming of Objectivity – the Myth of a Profession - Jevtović, Zoran B. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
Reporting is usually seen as a process in which different facts get sense and specific meaning in a society. The complex nature of media discourse turns occurrences, conflicts, processes and individuals into news, reports, interviews an other genres. The whole process was for a long time followed by understanding objectivity as one of crucial postulates in journalism. During the centuries developed a specific myth of good journalism, that promote honesty, balancing, fair play, impartiality, in a word – objectivity. However, globalization and the digital revolution, supported by corporate capital point out the manipulative context and ideological construct of contemporary media practice, that structuring and distribution of information subordinate to the interests of the ruling elites. In new journalism, visible and invisible are blended in convincing narrative, reconstructed image persuade critical thinking, and ideological concepts are hidden by lexical meaning. Between archaic desire to transmit the truth, with full consideration of professional standards, and clientelistic journalism, which develops a close relationship with advertisers and media owners, expands unbridgeable gap, which significantly changes the character of journalism across the globe.